Disentangling the Dyadic Dance: Theoretical, Methodological and Outcomes Systematic Review of Mother-Infant Dyadic Processes - Provenzi, Livio; Scotto di Minico, Giunia; Giusti, Lorenzo; Guida, Elena; Müller, Mitho (Frontiers in Psychology, 2018)
Background. During the last decades, the research on mother-infant dyad has produced a great amount of data, methods and theories, which largely contributed to set a revolution in the way we look at developmental changes during infancy and childhood. Very different constructs depict the different aspects of the “dyadic dance” occurring between a mother and her infant; nonetheless, a comprehensive and consistent systematization of these concepts in a coherent theoretical landscape is still lacking. Aim. In the present work, we aim at disentangling the different theoretical and methodological definitions of 9 dyadic constructs and we highlight their effects on infants’ and children developmental outcomes. Methods. A literature search has been conducted on three databases – PubMed, Scopus, Web of Science. Three different reviews are reported here: (1) a review on the theoretical definitions of dyadic constructs; (2) a review of operational definitions, settings and methods of dyadic processes; (3) a systematic review of dyadic processes’ outcomes for infants’ and children developmental trajectories. Results. Two constructs emerged as wide meta-theoretical concepts (reciprocity and mutuality) and seven described specific processes (attunement, contingency, coordination, matching, mirroring, reparation, synchrony). A global model resuming the relationships among different processes is reported, which highlights the emergence of two specific cycles of dyadic functioning (i.e., matching-mismatching-reparation-synchrony; contingency, coordination, attunement, mirroring). A comprehensive review of the adopted measures is also provided. Finally, all the processes provided significant contributions to infants’ behavioral, cognitive, and socio-emotional development during the first 3 years of age, but limited research has been conducted on specific processes (e.g., reparation and mirroring). Conclusion. The present study provides an original research-grounded framework to consider the different nature of mother-infant dyadic processes within a unified dyadic eco-system. Different levels of evidence emerged for the role of diverse mother-infant dyadic processes on infants’ and children development. Open questions and future research directions are highlighted.